2014
DOI: 10.12691/ajfst-2-3-3
|View full text |Cite
|
Sign up to set email alerts
|

<i>Aloe vera</i> gel as a Novel Edible Coating for Fresh Fruits: A Review

Abstract: New technological advances in antimicrobial edible coatings for food may hold promise in extending shelf life, reducing packaging layers, meeting food safety and quality requirements. Emerging research shows polysaccharides, bacteriocins, essential oils, enzymes, proteins and lipids are all natural coatings that have unrealized potential in food preservation. Recently, interest has increased in using Aloe vera gel-based edible coating material for fruits and vegetables. Aloe vera gel has been proven one of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(92 citation statements)
references
References 29 publications
4
85
0
3
Order By: Relevance
“…Another exceptional case are gels and aqueous extracts from the leaves of the plant Aloe vera, which are edible and can also be used to coat fresh or minimally processed horticultural products. These coatings have been basically used for physiologic preservation of fruit after harvest, but they are also known for their antimicrobial activity [66][67][68]. However, in contrast to chitosan-based coatings, there is very limited information on the performance of coatings based on A. vera gels against fungi causing postharvest decay of citrus fruit.…”
Section: Types Of Antifungal Ingredientsmentioning
confidence: 99%
“…Another exceptional case are gels and aqueous extracts from the leaves of the plant Aloe vera, which are edible and can also be used to coat fresh or minimally processed horticultural products. These coatings have been basically used for physiologic preservation of fruit after harvest, but they are also known for their antimicrobial activity [66][67][68]. However, in contrast to chitosan-based coatings, there is very limited information on the performance of coatings based on A. vera gels against fungi causing postharvest decay of citrus fruit.…”
Section: Types Of Antifungal Ingredientsmentioning
confidence: 99%
“…Aloe vera gel has been proven one of the best edible and biologically safe preservative coatings for different types of foods because of its film-forming properties, antimicrobial actions, biodegradability and biochemical properties. It is composed mainly of polysaccharides and acts as a natural barrier to moisture and oxygen, which are the main agents of deterioration of fruits and vegetables (Misir et al, 2014). Aloe vera gel coatings have a various favorable effect on fruits such as imparting a glossy appearance and better color, retarding weight loss, or prolonging storage/shelf-life by preventing microbial spoilage (Dang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Aloevera gel has been proven one of the best edible and biologically safe preservative coatings for different types of foods because of its film-forming properties, antimicrobial actions and biodegradability and biochemical properties. It is composed mainly of polysaccharides and acts as a natural barrier to moisture and oxygen, which are the main agents of deterioration of fruits and vegetables (Misir et al, 2014). Aloevera gel coatings have a various favorable effect on fruits such as imparting a glossy appearance and better color, retarding weight loss, or prolonging storage/shelf-life by preventing microbial spoilage (Dang et al, 2008) and has found to be effective in fruits such as table grapes (Castillo et al, 2010), sweet cherries (Martinez et al, 2006) and nectarines (Ahmed et al, 2009).…”
Section: Issn: 2319-7706 Volume 7 Number 01 (2018)mentioning
confidence: 99%